Peran Perawat Dalam Uji Kompetensi Internasional “NCLEX RN” : Literature Review - Khoiriyah, Siti; Indriyani, Farihah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2017)
Nursing education is designed not only to improve science. Nurses can know the basic science and applied science as a health worker (learn to know) or just have the skills to run various procedures nursing service. Nurses at the world level have decreased, the need for nurses is increasing due to several factors, namely the increasing variety of diseases, the increasing of the elderly population and the increasing number of nurses approaching retirement age. Buerhaus (2000) in Marie Kline (2010) mentioned in his research that 1 in 4 nurses this year is predicted to be 50 years or older. In addition 30% of senior nurses who have obtained RN licenses intend to leave the nursing profession within the next 3 years (Buerhaus, Donelan, Ulrich, Norman, &Dittus, 2006 in Marie Kline, 2010) nurses according to their duties and roles in the nursing pratik environment (learn to do). One effort to improve the quality of nurses is to improve the nursing students' graduation in the NCLEX-RN test (Marie Kline, 2010). NCLEX is a test system to determine the ability of a nurse, both cognitively, skill (ability to perform nursing procedures) and attitude (attitude) so as to provide care nursing safely and effectively at all levels of nursing services. NCLEX exam results will be the basis for the NCSBN in licensing as PN / Practical Nursing or RN / Register Nurse. Keywords: nurse, RN, NCLEX, competency test.